Forests, Water and People in the Humid Tropics 2005
DOI: 10.1017/cbo9780511535666.039
|View full text |Cite
|
Sign up to set email alerts
|

Parsimonious spatial representation of tropical soils within dynamic rainfall—runoff models

Abstract: Introduction Models are used increasingly to simulate hydrological processes within tropical regions. There is now a wealth of publications addressing evaporation modelling (particularly wet-canopy evaporation) of local areas of tropical forest in, for example, Niger (Gash et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 80 publications
0
17
0
Order By: Relevance
“…Figure 8 shows the measured Ks of the Danum soil profile after being up-scaled to a lateral Ks value (adapted from Chappell et al, 1998Chappell et al, , 2004b. The broken line in the same figure shows the effective lateral Ks values derived from inversion of a catchment model (TOPMODEL) applied to rainfall-runoff data from the Baru catchment (similarly adapted from Chappell et al, 1998Chappell et al, , 2004b. The latter implicitly includes the dominant runoff pathways (thus, potentially, the effects of soil piping) on catchment-scale runoff generation.…”
Section: Impact Of Lateral Pipes On Effective Ks Of Humid Tropical Himentioning
confidence: 99%
“…Figure 8 shows the measured Ks of the Danum soil profile after being up-scaled to a lateral Ks value (adapted from Chappell et al, 1998Chappell et al, , 2004b. The broken line in the same figure shows the effective lateral Ks values derived from inversion of a catchment model (TOPMODEL) applied to rainfall-runoff data from the Baru catchment (similarly adapted from Chappell et al, 1998Chappell et al, , 2004b. The latter implicitly includes the dominant runoff pathways (thus, potentially, the effects of soil piping) on catchment-scale runoff generation.…”
Section: Impact Of Lateral Pipes On Effective Ks Of Humid Tropical Himentioning
confidence: 99%
“…0.1-50 km 2 ) in the wet tropics has sufficient data on soil/rock characteristics, soil depths, soil surface characteristics and canopy characteristics, to allow accurate physics-based modelling of distributed water pathways to be made (see e.g. Beven, 2000Beven, , 2001bBeven, , 2002Chappell et al, 1998Chappell et al, , 2004cChappell and Sherlock, 2005;Croke et al, 2004). Without reliable estimates of parameter values representative of the whole catchment, forest use/change predictions become unrealistic.…”
Section: Value Of Dbm Models Over Models Which Have a Priori Assumptimentioning
confidence: 99%
“…Bathurst et al, 2004;Ott and Uhlenbrook, 2004). More recently, other scientists have, however, suggested that these physics-based catchment models may not be giving reliable results of hydrological change following forestry or other land cover/use change scenarios due largely to the large uncertainties in the calibrated parameter values (Parkinson and Young, 1998;Beven, 2001a,b;Beven and Freer, 2001;Chappell and Fowell, 2003;Chappell et al, 2004c). Models requiring calibration of a smaller number of parameter estimates thus giving smaller uncertainty have started to be used to simulate land cover/use change scenarios.…”
Section: Value Of Dbm Models Over Models Which Have a Priori Assumptimentioning
confidence: 99%
See 2 more Smart Citations